The Pedagogy of the Job Guarantee - Feinig, Jakob; Valayden, Diren (Radical Teacher, 2021)
In this article, we offer a pedagogical framework that explores possibilities for the democratic control over socio-economic life via a Job Guarantee (JG), the legally guaranteed and publicly financed right to productive work with benefits wherever one lives, or wants to live. In the first part of the JG project, students interview local leaders and residents to gauge what people can do for each other. Through these interviews, students and community members identify untapped possibilities and think about matching local needs with local skills in a collaborative process. The interviews and other class activities are designed to familiarize students with the JG framing that sees unemployed people as an asset not a burden. This framework challenges the dehumanizing idea that people can be superfluous, useless, a threat, or a burden. We also situate the JG as part of Modern Monetary Theory (MMT) and discuss money as a governance mechanism that enables people to organize, and potentially democratize, socio-economic life.